Analysis of the Potential and Impact of Utilizing Nickel Slag Powder and Recycled Plastic on the Technical Properties of Concrete Blocks: In Terms of Strength and Cost Efficiency - Nelfia, Lisa Oksri; Rahman, Muhammad Rifqon Fahrezza; Adijaya, Krisma; Sunarno, Yohans (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Plastic waste and nickel slag are significant environmental pollutants, while the construction sector demands sustainable building materials. This study investigates the use of nickel slag powder as a partial cement replacement and recycled High-Density Polyethylene (HDPE) plastic as a partial replacement for fine aggregate in concrete block production. Laboratory tests were conducted in accordance with SNI standards for compressive strength, splitting tensile strength, porosity, permeability, and cost. Results showed that low substitution levels (2.5–10%) improved both strength and durability. The highest compressive strength of 10.43 MPa was achieved at a 5% substitution level, compared to 7.13 MPa in the control mix, while the maximum tensile strength of 1.32 MPa was observed at a 2.5% substitution level. Porosity was reduced to 0.97% and permeability to 4.13 × 10⁻⁷ cm/s, indicating a denser microstructure. Cost analysis revealed a reduction from Rp9,128.80 per block (0% substitution) to Rp8,252.36 at 10%, yielding savings of about 9.6%. However, higher substitution levels (>10%) led to strength loss and increased porosity due to incomplete hydration and weak bonding. The results confirm that the optimal substitution range of 2.5–10% balances performance and cost, providing an eco-friendly and cost-effective solution for sustainable concrete block production within a circular economy framework.